The Importance of Sports Activities in the Formation of Skills for an Active and Healthy Lifestyle in Young People - V. Lesco; V. Razmiret (Bulletin of the Transilvania University of Braşov: Series IX Sciences of Human Kinetics)
Sports activities play a crucial role in developing the skills for an active and healthy lifestyle in adolescents, providing students with the opportunity to experience and engage in a variety of activities in order to develop their motor, social, and intellectual skills. The purpose of the paper is to highlight the essential role that sports activities have in skills training, necessary for an active and healthy lifestyle in adolescents. The objectives of the research include examining the physical benefits of sports activities on the health of adolescents, highlighting the development of motor skills through sports activities, and analyzing the impact of sports activities on the social and emotional development of adolescents, especially through identifying strategies and resources available to encourage adolescents to participate in sports activities and adopt an active and healthy lifestyle. Sports activities are essential for training the skills for an active and healthy lifestyle in adolescents, contributing to the improvement of physical and mental health, the development of social and emotional skills, and the increase of self-confidence and self-esteem.